2021
DOI: 10.1111/ddg.14566
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of dermatomyositis patients with and without associated malignancy

Abstract: Background: Dermatomyositis belongs to the rare idiopathic, inflammatory myositis group. A previously postulated link between some cases of dermatomyositis and malignancy has been established in recent years. Criteria suggestive of a malignancy association are still being explored. Patients and Methods:We retrospectively analyzed data from 63 patients with dermatomyositis over a period of 15 years. Results:The following criteria argue for cancer-associated dermatomyositis: older age (> 52 years [P = 0.001], > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 41 publications
3
17
0
1
Order By: Relevance
“…Fiorentino et al reported that characteristic cutaneous features have been reported, including psoriasiform lesions or so called ‘red-on-white’ patches (hypopigmented macules/patches associated with focal, often follicular, telangiectatic erythema) [ 22 ]. Our patients’ cutaneous manifestations were similar to those in the reports [ 17 , 18 , 19 , 20 , 21 , 22 ], but these findings were severe compared with those in patients with TIF-1γ-negative DM. For example, skin lesions tended to be widespread, more dark-red in color, and scattered throughout the body.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Fiorentino et al reported that characteristic cutaneous features have been reported, including psoriasiform lesions or so called ‘red-on-white’ patches (hypopigmented macules/patches associated with focal, often follicular, telangiectatic erythema) [ 22 ]. Our patients’ cutaneous manifestations were similar to those in the reports [ 17 , 18 , 19 , 20 , 21 , 22 ], but these findings were severe compared with those in patients with TIF-1γ-negative DM. For example, skin lesions tended to be widespread, more dark-red in color, and scattered throughout the body.…”
Section: Discussionsupporting
confidence: 89%
“…One published series of patients with DM reported an incidence of cancer ranging from 9% to 42% [ 15 , 16 ]. The most frequent are ovarian, breast, lung, gastric, and colorectal tumors, as well as lymphomas in dermatomyositis, lung and urinary bladder cancers, and lymphomas in polymyositis [ 18 ]. Most cancers preceded, occurred concurrently, or occurred after the onset of DM, but is usually recognized within 3 years of DM diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations